The Integration of Freud’s Concept of Personality Structure and the Nafs in the Qur’an: A Study of Islamic Psychology from the Perspective of Ulil Albab - Ahmad Fikri Nur Muzacky; Moch Taufiq Ridho (Westscience Press, 2026)
Psychology as a widely studied academic discipline has undergone a fundamental shift throughout its history. Originally dedicated to exploring the nature of the soul (psyche), contemporary psychology has largely abandoned this dimension, redirecting its focus entirely toward the study of organismic behavior. This shift culminated in Sigmund Freud's psychoanalytic theory, which constructs human personality through the concepts of id, ego, and superego in a framework entirely devoid of spiritual dimensions, even dismissing religion as mere delusion. This study aims to restore the existence of psychology as a science of the soul by examining its relevance through the integration of Freud's personality structure and the Qur'anic concept of nafs (nafs ammarah, nafs lawwamah, and nafs muthmainnah) within the perspective of Ulil Albab. A library research approach was employed, systematically analyzing psychological literature, Islamic scholarship, and empirical studies related to both frameworks. The findings reveal significant points of convergence between the two concepts, alongside fundamental differences: Qur'anic personality is theocentric, dynamic, and open to divine dimensions, whereas Freudian personality is anthropocentric, static, and closed to spiritual dimensions. The Ulil Albab perspective proves to be a productive integrative framework — embracing the positive contributions of Western psychology while enriching and completing them with the depth of Qur'anic nafs concepts, enabling the study of human personality to return to its spiritual essence.